2011
DOI: 10.1002/anie.201106917
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Impurities in Graphenes Prepared from Graphite Can Dramatically Influence Their Properties

Abstract: All at C? Graphenes prepared by the top-down exfoliation of graphite are shown to contain metallic impurities (see scheme, metal impurities shown as black dots). These impurities may dominate their properties and can have a negative influence on their potential applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 49 publications
(24 reference statements)
2
119
0
Order By: Relevance
“…Many papers reported their excellent electrochemical properties [15,16]. However, a high expectation for CNTs and graphene had to be lowered when some inspiring papers reported that the impurities within CNTs and graphene influenced their redox properties and even dominated their electrochemical responses [17][18][19][20]. So, it is necessary to develop new carbon electrode nanomaterials with high purity to avoid disputes.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers reported their excellent electrochemical properties [15,16]. However, a high expectation for CNTs and graphene had to be lowered when some inspiring papers reported that the impurities within CNTs and graphene influenced their redox properties and even dominated their electrochemical responses [17][18][19][20]. So, it is necessary to develop new carbon electrode nanomaterials with high purity to avoid disputes.…”
Section: Introductionmentioning
confidence: 99%
“…As it can be seen in Table SI5 when the acidity of the organic compound increases the conversion of 1 also increased, although the product distribution was somewhat different that when the OD of 1 was promoted using a carbocatalysts. It is worth commenting that previous studies in the literature have shown that GO can act as acid catalyst, [21,22] for instance for the conversion of carbohydrates into hydroxymethylfurfural derivatives [23] , due to the presence of residual hydrogensulfate groups. However, in the present study it should be mentioned that besides GO, other G types that have not been exposed to sulfuric acid also exhibit catalytic activity (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A large part of these metals are introduced in the GO sample during Hummers graphite oxidation using an excess of KMnO4 as strong oxidant, but starting graphite also contains a detectable concentration of Fe. [25] A percentage of these metals remains, probably as cations associated to carboxylate groups, during purification of GO. Considering the general high catalytic activity of transition metals promoting aerobic oxidations, it could be that the presence of these metals, even at the trace level could be the real active site responsible for the OD of 1.…”
Section: Resultsmentioning
confidence: 99%
“…[5,27,57] However, in none of the cases of claimed "metal-free" ORR catalysis do the authors attempt to determine the amount of metals in the doped graphene material. It has been shown by us and by others that metals at trace levels remain in graphene prepared from either synthetic [58] or natural graphite [59] through oxidative treatment, [60] or in CVD graphene, [61,62] and it is introduced to graphene, even ultrapure graphite, through contamination from reagents used for graphite treatment. [63] Metallic impurities are even found in graphene inks used for the preparation of screen-printed electrodes.…”
Section: P-doping For Metal-free Electrocatalysismentioning
confidence: 99%